V/W-band satellite communication systems - Mendez, Zachary, author; Chandrasekaran, Venkatachalam, advisor; Cheney, Margaret, committee member; Siller, Thomas, committee member (Colorado State University. Libraries, 2021)
The increasing demand for high-speed wireless communications are driving new innovations and developments in telecommunications engineering. Telecommunication systems are taking advantage of the developments in manufacturing and integrated circuit design to provide improved communication system performance. Contemporary satellite communication systems typically operate in the frequency regions between S-band and Ku-band. Improved manufacturing techniques are allowing for systems to be reliably constructed to operate in the millimeter wave frequency bands, which inherently increases data rates by increasing the available bandwidth, and improving wireless communication system efficiency. High throughput satellites are being developed to utilize these higher frequencies, and employ multiple access techniques to provide more capabilities for users. The future of satellite communications will utilize V/W-band communication systems to increase the available bandwidth and realize more effective communication and radar systems. This thesis presents the system design and development of a V/W-band multiple-input multiple-output (MIMO) antenna system. The multibeam feed assembly development is presented from the initial stages of design and simulation, to the building and testing of waveguide prototypes, and through integration into a full-scale antenna system that is built and tested at a near-field antenna range for a system demonstration. The system demonstration includes frequency mixing modules to serve as the communication interface, the multibeam feed horn assembly, and an offset fed parabolic reflector. The system measurements are compared to simulated results obtained with CST Microwave Suite® for system validation.
Keywords: V/W-band; MIMO